2022
DOI: 10.3390/ncrna8020021
|View full text |Cite
|
Sign up to set email alerts
|

ABHD11-AS1: An Emerging Long Non-Coding RNA (lncRNA) with Clinical Significance in Human Malignancies

Abstract: The aberrant expression of lncRNAs has been linked to the development and progression of different cancers. One such lncRNA is ABHD11 antisense RNA 1 (ABHD11-AS1), which has recently gained attention for its significant role in human malignancies. ABHD11-AS1 is highly expressed in gastric, lung, breast, colorectal, thyroid, pancreas, ovary, endometrium, cervix, and bladder cancers. Several reports highlighted the clinical significance of ABHD11-AS1 in prognosis, diagnosis, prediction of cancer progression stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 100 publications
(186 reference statements)
1
5
0
Order By: Relevance
“…The intracellular domain of ACE2 preferentially formed an immune complex with the GTP-bound, endogenous Ras, which can become formed in the presence of excessive GTP (Figure 4B). Similar results were obtained in the case of the interaction with endogenous Ras downstream effectors phosphoinositide 3-kinase α and β (Figure S4; Figure S5), which are known to be direct upstream regulators of Akt kinase [19][20][21][24][25][26][27]. Taken together with the above results, it is suggested that Ras and the Ras signaling complex can be trapped to ACE2.…”
Section: Ace2 Preferentially Interacts With An Active Gtp-bound Ras T...supporting
confidence: 85%
“…The intracellular domain of ACE2 preferentially formed an immune complex with the GTP-bound, endogenous Ras, which can become formed in the presence of excessive GTP (Figure 4B). Similar results were obtained in the case of the interaction with endogenous Ras downstream effectors phosphoinositide 3-kinase α and β (Figure S4; Figure S5), which are known to be direct upstream regulators of Akt kinase [19][20][21][24][25][26][27]. Taken together with the above results, it is suggested that Ras and the Ras signaling complex can be trapped to ACE2.…”
Section: Ace2 Preferentially Interacts With An Active Gtp-bound Ras T...supporting
confidence: 85%
“…Not much is known on the function of long non-coding RNA (lncRNA) Abhd11os ( 139 ) in astrocytes. The human homolog ABHD11 antisense RNA 1 (ABHD11-AS1) was found to be highly expressed in gastric, lung, breast, colorectal, thyroid, pancreas, ovary, endometrium, cervix, and bladder cancer and was therefore suggested as biomarker for diagnosis and prognosis ( 140 ). In mouse models of Huntington's disease, expression of Abhd11os was reduced ( 139 ) or dysregulated ( 141 ) and its overexpression had neuroprotective effects in mice against mutant huntingtin-induced toxicity ( 139 ).…”
Section: Discussionmentioning
confidence: 99%
“…ABHD11-AS1, an important promoter in human malignancies, is located at 7q11.23 and is known as the long intergenic non-coding RNA 35 (LINC00035) and Williams–Beuren syndrome chromosome region 26 (WBSCR26) RNA gene. A number of studies in recent years have shown that ABHD11-AS1 is a potential biomarker for early diagnosis of CC ( Golla et al, 2022 ). Zhu et al (2022 ) observed increased lncRNA ABHD11-AS1 and decreased miR-1254 in the serum of CC patients compared with healthy controls, suggesting that dysregulation of ABHD11-AS1 and miR-1254 is involved in CC progression.…”
Section: Mechanisms Relating To Lncrnas In CCmentioning
confidence: 99%